An efficient polysulfide trapper of an nitrogen and nickel-decorating amylum scaffold-coated separator for ultrahigh performance in lithium–sulfur batteries. Issue 3 (2nd January 2020) - Zuo, Yinze; Zhao, Meng; Ren, Peijia; Su, Weiming; Zhou, Jian; Chen, Yanbin; Tang, Yuefeng; Chen, Yanfeng
Abstract : The powerful chemical affinity and catalysis of the N, Ni-decorating amylum for LiPSs realize a cell with high performance. Abstract : In recent years, lithium–sulfur batteries (LSBs) have attracted increasing attention due to their extraordinary theoretical capacity, high energy density, eco-friendliness and the low cost of sulfur. However, increasing the sulfur loading and restraining the polysulfide shuttle effect are the primary issues to be solved. Herein, a novel N, Ni-decorating amylum scaffold was fabricated by carbonizing amylum with urea and NiCl·6H2 O (AC/Ni/N) at 1000 °C under Ar atmosphere. The AC/Ni/N scaffold was used to modify the separator as an effective polysulfide trapper for LSBs. This AC/Ni/N-modified separator not only exhibits a high polysulfide confinement, but provides abundant conductive pathways to permit the fast diffusion of the Li + ions and electrons. Importantly, the synergistic catalysis of the Ni nanoparticles and N atoms plays a key role in improving the reaction kinetics of LSBs. Consequently, the LSBs with AC/Ni/N-modified separators delivered a superior rate performance and ultra-long cycling life with a very low decay rate of 0.043% per cycle at 4C. Moreover, the cathode, with a high sulfur loading at 7 mg cm −2 and low electrolyte environment at 7.8 μL mg −1, delivered a high discharge capacity of 714 mA h g −1 after 100 cycles.